SELF-ESTEEM AND TRAIT ANXIETY IN GIRLS PRACTICING COMPETITIVE AND RECREATIONAL GYMNASTICS - Olivia Donti; Kalliopi Theodorakou; Spiros Kambiotis; Anstasia Donti (Science of Gymnastics Journal)
The purpose of this study was to examine self-esteem and trait anxiety in 161 girls, 10-12 years old, practising competitive and recreational gymnastics sports. To measure self-esteem and trait anxiety, the Greek versions of Harter’s Self-Perception Profile for Children (1985a) and of the State-Trait Anxiety for Children (STAIC; Spielberger, Edwards, Lushene, Montuori, & Platzek, 1973) were used respectively. A MANOVA and an independent samples t-test were performed in order to examine differences in self-esteem and trait anxiety between the two groups of gymnasts respectively. Results indicated that there was no significant difference between competitive and recreational gymnasts in self-esteem except for the subscales of scholastic competence, and social acceptance, which had lower values for the competitive girls. However, girls participating in competitive gymnastics sports had significantly higher values of trait anxiety compared to girls practising recreational gymnastics sports. Further research is required on the impact of competitive sport effect on gymnasts’ psychological parameters.